2013
DOI: 10.1111/srt.12082
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the stratum corneum thickness measured in vivo with confocal Raman spectroscopy and confocal reflectance microscopy

Abstract: Both methods, CRS and CLSM, were found to be suitable to measure SC thickness correctly. Therefore, when using CRS, for example to obtain detailed information about the molecular composition of the skin, it is additionally possible to accurately measure SC thickness with the same device to have an orientation in which skin layer molecules are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 19 publications
1
57
0
Order By: Relevance
“…The SC was divided into three equally spaced compartments (22), and the change in water content within each SC compartment was calculated according to the area under the curve (AUC) (20). In addition, the water gradient (slope of water increase) from outer to inner SC and SC thickness were calculated (20,21).…”
Section: Subjects and Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SC was divided into three equally spaced compartments (22), and the change in water content within each SC compartment was calculated according to the area under the curve (AUC) (20). In addition, the water gradient (slope of water increase) from outer to inner SC and SC thickness were calculated (20,21).…”
Section: Subjects and Assessmentsmentioning
confidence: 99%
“…Raman spectroscopy, an established noninvasive method (18,19), was used to evaluate the change in water distribution within the SC after a single application of NTP-CE. Approximately 10 water profile measurements were performed in the center of each test area per assessment time as described before (20,21), thereby investigating the skin down to a depth of about 30 lm. The SC was divided into three equally spaced compartments (22), and the change in water content within each SC compartment was calculated according to the area under the curve (AUC) (20).…”
Section: Subjects and Assessmentsmentioning
confidence: 99%
“…The white spots in (c) and Typically, LPs of the SC in broad area are related to skin barrier function. In addition to OCT methods, a-TT of the SC was indirectly verified via z-axial population of water content by confocal Raman spectroscopy [13,16] or was directly measured by multiphoton laser tomography [17,18]. For confocal Raman spectroscopy and confocal reflectance microscope [16], they both need the database of a-NOLs from frozen section [19] to verify the a-CLT of SC.…”
Section: Introductionmentioning
confidence: 99%
“…SC thickness on human forearm, palm, cheek and lower leg were also studied to determine by using two non-invasive measuring techniques namely, confocal Raman spectroscopy and confocal laser scanning microscopy, to measure SC thickness which were then compared to the thickness in literature data. It was found that it was possible to accurately measure the SC thickness with both techniques (Bohling et al, 2013).…”
Section: Mechanical Properties Of Skinmentioning
confidence: 99%